Clinical Outcomes After Chronic Distal Biceps Reconstruction With Allografts. (October 2013) - Snir, Nimrod; Hamula, Mathew; Wolfson, Theodore; Meislin, Robert; Strauss, Eric J.; Jazrawi, Laith M.
Background: Chronic ruptures of the distal biceps are often complicated by tendon retraction and fibrosis, precluding primary repair. Reconstruction with allograft augmentation has been proposed as an alternative for cases not amenable to primary repair. Purpose: To investigate the clinical outcomes of late distal biceps reconstruction using allograft tissue. Study Design: Case series; Level of evidence, 4. Methods: A total of 20 patients who underwent distal biceps reconstruction with allograft tissue between May 2007 and May 2012 were identified. Charts were retrospectively reviewed for postoperative complications, gross flexion and supination strength, and range of motion. Subjective functional outcomes were assessed prospectively with the Mayo Elbow Performance Score (MEPS) and Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. Results: Eighteen patients with adequate follow-up were included in the study. All had undergone late distal biceps reconstruction with allografts (Achilles [n = 15], semitendinosus [n = 1], gracilis [n = 1], or anterior tibialis [n = 1]) for symptomatic chronic ruptures of the distal biceps. At a mean office follow-up of 9.3 months (range, 4-14 months), all patients had full range of motion and mean gross strength of 4.7 of 5 (range, 4-5) in flexion and supination. After a mean out-of-office follow-up at 21 months (range, 7-68.8 months), the mean DASH score was 7.5 ± 17.9, and the mean MEPS increased from 43.1 preoperatively to 94.2 postoperatively ( P < .001). The only complication observed was transient posterior interosseous nerve palsy in 2 patients. Additionally, all but 1 patient reported a cosmetic deformity. However, all patients found it acceptable. Conclusion: Late reconstruction for chronic ruptures of the distal biceps using allograft tissue is a safe and effective solution for symptomatic patients with functional demands in forearm supination and elbow flexion. While there are several graft options, the literature supports good results with Achilles tendon allografts. Further studies are needed to evaluate the clinical outcomes of other allograft options.